The Effect of Customer Relationship Marketing Commitment, Communication, and Satisfaction on Customer Loyalty : Case Study on Scarlett Whitening in the city of South Tangerang - Risa Novia Pratama Sari; Fendi Saputra (RTTM, 2023)
This research is motivated by low communication in the retail business in terms of service from employees to customers. This affects the decline in customer satisfaction and causes customer loyalty is at a very low level. The research aims to find out and analyze how significant the influence of Commitment (X1) , Communication (X2), and Satisfaction (X3 ) on Customer P Loyalty (Y) . The research was conducted in October - November 20 22 in the city of South Tangerang. The research method used in This research is quantitative using a questionnaire filled in directly by Scarlett Whitening users with a total population of 19,920 people and a sample of 111 people calculated using descriptive (demographic) test , data instrument test , validity and reliability test , classical assumption test , normality test, multicollinearity , multiple linear analysis , hypothesis test , coefficient of determination test (R-square - adjusted R-square), F test (anova), t test (coeffients) were performed in this study using data processed using the SPSS (Statistical Product and Service Solution) version 16.0. The results of this study indicate that Commitment has significant influence on Customer Loyalty , Communication has influence significantly on Customer Loyalty , and Satisfaction _ have a significant influence . Thus, this study shows that Communication, Commitment , and Satisfaction have a significant effect on Customer Loyalty .